HUBUNGAN PENGETAHUAN DAN SIKAP IBU HAMIL DENGAN KEPATUHAN MENGKONSUMSI TABLET TAMBAH DARAH DI PUSKESMAS KOTO BARU KABUPATEN DHARMASRAYA TAHUN 2022 - Rati Purwati; Dona Nopidayani (Nusantara Hasana Journal, 2022)
Blood Supplement Tablets (Fe) are the provision of iron folate in the form of tablets, each tablet of 60 mg elemental iron and 1.25 mg folic acid, which is given by the government to pregnant women to overcome the problem of anemia in pregnant women, these substances are needed in hemopobesis. formation of blood), namely in the synthesis of hemoglobin Hb. Iron, which is found in all body cells, plays an important role in various biochemical reactions, including the production of red blood cells. These cells are treated to lift oxygen throughout the body’s tissues. This research was conducted in May 2022. This research was conducted in the Koto Baru Health Center Working Area, Dharmasraya Regency. This study uses a cross-sectional study method that aims to collect data or collect information on pregnant women. The statistical test used was the chi-square test, the sampling technique used was probability sampling using the "Random Sampling" method. Through data analysis with statistical tests using the chi-square test with 47 pregnant women, the results obtained were pregnant women most mothers have less knowledge, namely 28 people (59.6%). Based on the results of statistical tests, the p-value = 0,2008 (P value < 0.05) means that there is no significant relationship between knowledge and consuming blood-added tablets in the working area of ​​Koto Baru Public Health Center, Dharmasraya District 2022. Based on the results of statistical tests with using the chi square test, the p-value = 0.308> 0.005 means that there is no significant relationship between mother’s attitude and adherence to consuming blood-added tablets in the work area of ​​the Koto Baru Public Health Center in 2022. The conclusion of this study is that most pregnant women have less knowledge about consuming blood-added tablets. which means between the attitude of pregnant women with adherence to consuming blood-added tablets.